Comparative Effectiveness of Direct Oral Anticoagulants versus Vitamin K Antagonists on the Incidence of Dementia in Patients with Non-Valvular Atrial Fibrillation: A Systematic Review and Meta-Analysis - Melany Nurjanah; Haryadi (The International Journal of Medical Science and Health Research, 2025)
Introduction: Atrial fibrillation (AF) is an established independent risk factor for cognitive decline and dementia. While oral anticoagulation is known to mitigate this risk compared to no treatment, the comparative effectiveness of direct oral anticoagulants (DOACs) versus vitamin K antagonists (VKAs) on cognitive outcomes remains a subject of ongoing investigation. This systematic review and meta-analysis aims to synthesize the current evidence comparing the effects of DOACs and VKAs on the incidence of dementia in patients with non-valvular atrial fibrillation (NVAF). Methods: A systematic literature search was conducted across PubMed, Google Scholar, Semantic Scholar, Springer, Wiley Online Library databases for randomized controlled trials and observational studies comparing DOACs with VKAs in adults with NVAF and reporting on incident dementia or other cognitive and clinical outcomes. The study was conducted in accordance with PRISMA guidelines. The primary outcome was incident all-cause dementia. Secondary outcomes included dementia subtypes (vascular, Alzheimer's), ischemic and hemorrhagic stroke, mortality, and major bleeding events. Adjusted hazard ratios (HRs) were pooled using a random-effects model. The Newcastle-Ottawa Scale was used to assess the risk of bias in observational studies. Results: A total of 16 observational cohort studies, encompassing over 1.5 million patients, were included in the final analysis. The pooled data demonstrated that treatment with DOACs was associated with a significantly lower risk of incident all-cause dementia compared to treatment with VKAs (Hazard Ratio 0.88, 95% Confidence Interval [CI] 0.80–0.98). The benefit was most pronounced for vascular dementia, where DOACs showed a significant risk reduction, whereas no significant difference was observed for Alzheimer's disease. Subgroup analyses revealed that the protective effect of DOACs was more evident in patients younger than 75 years (HR 0.86, 95% CI 0.81–0.92) and in Asian populations (HR 0.81, 95% CI 0.68–0.86). Consistent with their known safety profile, DOACs were associated with a significantly lower risk of intracranial hemorrhage (HR approximately 0.47) compared to VKAs Discussion: The findings suggest that the neuroprotective benefit of DOACs over VKAs is likely mediated through a more stable anticoagulation profile and a superior cerebral safety profile, particularly the marked reduction in both clinical and subclinical intracranial bleeding. The attenuated benefit in the elderly may reflect a higher burden of competing risks and non-AF-related dementia pathologies. The pronounced effect in Asian populations may be linked to pharmacogenomic factors affecting VKA metabolism. Conclusion: In patients with NVAF, the use of DOACs is associated with a lower incidence of dementia compared to VKAs. This finding supports the preferential use of DOACs, not only for their established stroke prevention efficacy and safety but also for their potential long-term cognitive benefits.